Perioperative outcomes of neoadjuvant chemotherapy plus camrelizumab compared with chemotherapy alone and chemoradiotherapy for locally advanced esophageal squamous cell cancer - Zhang, Baihua; Zhao, Hongbo; Wu, Xun; Gong, Lianghui; Yang, Desong; Li, Xu; Chen, Xiaoyan; Li, Jigang; Wang, Wenxiang; Wu, Jie; Xiao, Qin (Frontiers in Immunology, 2023)
Purpose Neoadjuvant chemoimmunotherapy (nCIT) is becoming a new therapeutic frontier for resectable esophageal squamous cell carcinoma (ESCC); however, crucial details and technical know-how regarding surgical techniques and the perioperative challenges following nCIT remain poorly understood. The study investigated and compared the advantages and disadvantages of esophagectomy following nCIT with neoadjuvant chemotherapy (nCT) and chemoradiotherapy (nCRT). Methods We retrospectively analyzed data of patients initially diagnosed with resectable ESCC at clinical stage T2-4N+ and received neoadjuvant therapy followed by esophagectomy at the Hunan Cancer Hospital between October 2014 and February 2021. Patients were divided into three groups according to neoadjuvant treatment: (i) nCIT; (ii) nCT; and (iii) nCRT. Results There were 34 patients in the nCIT group, 97 in the nCT group, and 31 in the nCRT group. Compared with nCT, nCIT followed by esophagectomy achieved higher pathological complete response (pCR; 29.0% versus 4.1%, p<0.001) and major pathological response (MPR; 52.9% versus 16.5%, p<0.001) rates, more resected lymph nodes during surgery (25.06±7.62 versus 20.64±9.68, p=0.009), less intraoperative blood loss (200.00±73.86 versus 266.49±176.29 mL, p=0.035), and comparable results in other perioperative parameters. Compared with nCRT, nCIT achieved similar pCR (29.0% versus 25.8%) and MPR (52.9% versus 51.6%, p=0.862) rates, with significantly more lymph nodes resected during surgery (25.06 ±7.62 versus 16.94±7.24, p<0.001), shorter operation time (267.79±50.67 versus 306.32±79.92 min, p=0.022), less intraoperative blood loss (200.00±73.86 versus 264.53±139.76 mL, p=0.022), and fewer ICU admissions after surgery (29.4% versus 80.6%, p<0.001). Regarding perioperative adverse events and complications, no significant statistical differences were detected between the nCIT and the nCT or nCRT groups. The 3-year overall survival rate after nCIT was 73.3%, slightly higher than 46.1% after nCT and 39.7% after nCRT, with no statistically significant differences (p=0.883). Conclusions This clinical analysis showed that nCIT is safe and feasible, with satisfactory pCR and MPR rates. Esophagectomy following nCIT has several perioperative advantages over nCT and nCRT, with comparable perioperative morbidity and mortality. The long-term survival benefits after nCIT still requires further investigation.